ASSA13-01-9 Risk Predictors of Acute Myocardial Infarction Mortality During Hospitalisation in Patients Aged 80 and Over. (29th April 2013) - Jing-guang, Luo; Ming, Yang; Ling, Han; Li-wei, Chen; Kang, Gao; Yan, Zhao; Wen-ze, Hu; Ping, Chen
Abstract : Objective: To explore the risk predictors of AMI mortality among hospital in patients aged 80 and over. Methods: In a cohort of AMI patients aged ≥80 years from 2003 to 2012 at CCU department in fuxing hospital, we explored the determinants to predict death risk among hospital. Variables examined included demographics, history, hemodynamic condition and laboratory results. Results: 386 patients presenting with AMI were enrolled. The hospital mortality rate was 23.3%. Multivariable stepwise regression analysis showed that eight independent significant predictors associated with mortality among hospital were history of stoke, cardiac shock, killip class III to IV, ventricular tachycardia, pulse rate ≥100 bpm and EF≤40% at presentation, in hospital bleeding, initial serum creatinine concentration ≥ 177umol/l and elevated initial WBC level. Hosmer-Lemeshow p value is 0.076 (chi-square: 12.871), which indicates good-fitness of the predict variables. Conclusions: Patients aged 80 and over have high mortality during hospitalisation, these risk prediction factors are clinically useful for predicting mortality in patients with AMI.